The Relationship Between Screen and Outdoor Time With Rates of Myopia in Spanish Children - Alvarez-Peregrina, Cristina; Sánchez-Tena, Miguel Ángel; Martinez-Perez, Clara; Villa-Collar, Cesar (Frontiers in Public Health, 2020)
Background: Nowadays, digital devices have become usual in children's lives around the world. Five percent of the children between 5 and 7 years old have their own smartphone and forty-two percent of them have their own tablet. This fact has produced a change in their lifestyle that can imply some risks, threats and/or opportunities. The light emitted by digital devices’ screens could involve, among others, possible risks to children’s vision. Methods: This study shows a detailed analysis of the vision of 7497 children between 5 and 7 years old carried out in the “Annual school campaign for children's visual health” in Spain during the years 2016, 2017 and 2019. The study connects the results in the visual screening with children's lifestyle, taking into account both, the number of hours per day that they use all digital devices and the daily time of outdoor exposure. Results: The study shows that children with myopia have more screen time use and shorter outdoor activity time when compared to those without myopia (p<0,01). Conclusions: Myopia in children is a public health problem and requires healthy lifestyle interventions at individual as well as at community level.